2008
DOI: 10.1007/s11240-007-9335-z
|View full text |Cite
|
Sign up to set email alerts
|

Sonication assisted Agrobacterium-mediated transformation enhances the transformation efficiency in flax (Linum usitatissimum L.)

Abstract: A sonication-assisted, Agrobacteriummediated, co-cultivation technique was used in an attempt to increase the transformation efficiency of flax. Hypocotyls and cotyledons excised from about 10-dayold flax seedlings grown in vitro were placed into a 10 mM MgSO 4 solution, and inoculated with an A. tumefaciens vector bearing the mgfp5-ER gene driven by the CaMV 35S promoter. The explants were subjected to pulses of ultrasound delivered by a sonicator apparatus (35 kHz) for 0-150 s and co-cultivated for 2 h at 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…However, the recovery of transgenic flax plants (13,16). When hypocotyl segments were directly inoculated, transgenic shoot frequency was extremely low due to the plant's defense mechanism caused by the pathogenic attack by the Agrobacterium infection (17).…”
Section: Resultsmentioning
confidence: 99%
“…However, the recovery of transgenic flax plants (13,16). When hypocotyl segments were directly inoculated, transgenic shoot frequency was extremely low due to the plant's defense mechanism caused by the pathogenic attack by the Agrobacterium infection (17).…”
Section: Resultsmentioning
confidence: 99%
“…However, our preliminary experiments demonstrated that ultrasound treatment and a subse quent immersion in A. tumefaciens suspension for inoculation was more effective than treatment with ultrasound concurrently with A. tumefaciens inocula tion.. We suggest that ultrasound treatment forms microwounds on the surface of PLBs and facilitates Agrobacterium infection. The ultrasound treatment was successfully employed to enhance transformation efficiency in several other plant species [7][8][9][10][11][12]. The impact of different ultrasonic power on transgenic 'Sanya' requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Pathak and Hamzah [6] found that in chickpeas the transformation efficiency was more than twice higher with SAAT treatment than at simple Agrobacterium transformation without soni cation. Subsequently, the ultrasound treatment was successfully employed to enhance transformation effi ciency in several plant species, both by direct DNA transfer to protoplasts and tissue cultures and by co cultivation with vector bacteria [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that no GUS expression was detected in the absence of SAAT, using the ordinary ''dipping'' method, demonstrating the relative recalcitrance of cacao to the practices of Agrobacteriummediated transformation. SAAT has been proved to be an efficient system of T-DNA delivery to cells in a number of plants (Santarém et al 1998;Tang et al 2001;Zaragozá et al 2004;Beranová et al 2008;de Oliveira et al 2009), especially those that are typically more recalcitrant to Agrobacteriummediated transformation (Trick and Finer 1997). This method involves subjecting the plant tissue to brief periods of ultrasound in the presence of Agrobacterium.…”
Section: Saatmentioning
confidence: 99%
“…It creates microwounding released from the cavitation of microbubbles causing minute visible wounds within and on the tissue (Gaba et al 2006). Such phenomena allow better access and infection of plant cells by Agrobacterium (Beranová et al 2008). In addition, the wounded tissue often produces inducers of the T-DNA transfer process, caused by the secretion of more phenolic compounds, enhancing the accessibility of putative cell wall binding factor to the Agrobacterium during transformation (Stachel et al 1985).…”
Section: Saatmentioning
confidence: 99%